The Influence of Service Quality and Brand Image on Patient Loyalty Mediated by Patient Satisfaction (An Empirical Study on Patients at “X” Hospital in East Bekasi) - Alfa Tiara Ramba; Liem Bambang Sugiyanto (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study aims to examine the effect of service quality and brand image on patient loyalty, with customer satisfaction as a mediating variable at X Hospital, East Bekasi, Indonesia. A quantitative survey was conducted using an online questionnaire distributed to 154 respondents who had received services at the hospital more than twice and were aged 17 years or older. Data were analyzed using Smart PLS 3. The results show that service quality and brand image significantly influence patient satisfaction, which, in turn, has a strong effect on patient loyalty. Both service quality and brand image also directly influence patient loyalty, with service quality identified as the strongest contributor, followed by brand image. Furthermore, patient satisfaction mediates the relationship between the independent variables and loyalty, confirming its critical role in shaping patient behavior. The study concludes that delivering high service quality and maintaining a positive brand image are essential strategies to enhance patient satisfaction and loyalty. Limitations of this study include its relatively small sample size and focus on a single hospital, restricting generalizability. Theoretically, the study contributes to the literature on patient loyalty by emphasizing the mediating role of satisfaction. Practically, it provides insights for hospital management to prioritize service improvements and strengthen brand perception. Future research is recommended to expand the sample across multiple hospitals and to explore additional mediating variables such as corporate reputation, perceived value, and revisit intention to provide a more comprehensive understanding of loyalty drivers.